Stuxnet Threat Analysis in SCADA (Supervisory Control And Data Acquisition) and PLC (Programmable Logic Controller) Systems - Zulfikar Sembiring (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2020)
This journal is devoted to the analysis of the Stuxnet malware known as (Win32 / Stuxnet) which has suddenly caught the attention of virus researchers in the last three years. In this journal, an overview of attacks targeted at the SCADA (Supervisory Control And Data Acquisition) system and PLC (Programmable Logic Controller) will be explained as the main targets of Stuxnet. Besides that, it will also explain the history of the development / variant of Stxunet and the prevention that can be done against the Stuxnet threat.